Trois perspectives lesbiennes féministes articulant le sexe, la sexualité et les rapports sociaux de sexe : Rich, Wittig, Butler - Brossard, Louise (Université du Québec à Montréal, 2004)
Keywords: IREF; approches et analyses; discipline; genre; hétérosexisme; identités; identités LGBTQIA2+; lesbianisme; mémoires/thèses; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

‘I am not Homophobic But...’: Disclaiming in Discourse Resisting Repeal of Section 28 - Burridge, Joseph (Sexualities, 2004)
This article attempts to take seriously the discourse of the morally conservative in the context of the failed repeal of Section 28 in the year 2000, and explores the operation of opposition to repeal which denied that homophobia was its motivation. It is argued that such disclaiming implies an orientation towards an attribution of homophobia as unhelpful or undesirable in this context. The failure of those advocating repeal to successfully problematize such arguments is deemed to reflect a collective ‘discourse of tolerance’ which assisted the arguments of those against repeal.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; homophobie; hétérosexisme; inégalités; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; section 28; soc2014; sociologie; systèmes d'oppressions; thématiques

Queer theory, butch/femme identities and lesbian space - Eves, Alison (Sexualities, 2004)
Queer theory has been criticized for its textual focus and lack of attention to the structural and to everyday social practices. This article is part of a wider attempt to draw on the different strengths and insights of queer theory and qualitative social sciences. I identify areas of intersection between them which suggest potential ways of developing a queer sociology. The article considers the negotiation of gender and sexual identity categories at the level of individual butch and femme identity narratives. The concept of interpretative repertoires is used to theorize the ways in which lesbians are both positioned by and actively negotiate particular discourses. I am interested in the spatial aspects of the negotiation and contestation of identities and the article examines the ways in which particular interpretative repertoires produce butch and femme metaphorical and material spaces. The article draws on a concept of space as fluid, contested in meaning and created through social interactions. The achievement of lesbian visibility is examined as a strategic intervention in the establishment of subcultural space in which lesbian genders may be performed and read in specifically lesbian ways. Butch and femme aesthetics are examined as tactics in resisting heterosexual space and demanding lesbian presence.
Keywords: approches et analyses; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques